A place called home look inside houses around the world - Baker, Kate (Lonely Planet Kids, 2020)
"Take a sneak peek inside homes from all around the world with this charming lift-the-flap book, written by Kate Baker and beautifully illustrated by Rebecca Green. From cozy wooden houses in snow-blanketed Greenland to traditional Maasai mud huts in East Africa, young children will discover different ways of living across the globe and get a unique glimpse into diverse cultures and communities. Suitable for children aged three and upwards, the colorful artwork is filled with fun details, helping to bring these miniature worlds to life. With flaps on every page allowing kids the chance to open doors, peep through windows and uncover what makes each distinct culture tick, this book encourages kids to be curious about our diverse world. Whether it's Mongolian yurts in the rolling plains of the Gobi Desert or raised jungle homes in the wilds of the Amazon Rainforest, A Place Called Home will take you on a journey all around the world to see how other people live." (Verlagsinformation)
Keywords: Sachbilderbuch